Effect of macrostructure on the thermoelectric properties of biomorphous SiC/Si ceramics - Kiselov, V.S.; Poludin, V.I.; Kiselyuk, M.P.; Kryskov, T.А.; Belyaev, A.E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
In this work, effect of porous macrostructure on the thermoelectric properties
of biomorphous SiC/Si ceramics prepared by the liquid silicon infiltration process has
been investigated. Temperature dependences of the conductivity and thermal e.m.f. have
been measured within the range 20-700 °C. It has been shown that electrical resistivity of
the samples decreases drastically as temperature increases over the entire temperature
range, indicating semiconductor behavior. All the samples demonstrate a negative
thermal e.m.f. confirming the electronic mechanism of charge transfer. It is ascertained
that anisotropy of porous macrostructure of the ceramics influences considerably on their
electric and thermoelectric properties. The figure of merit maximum value of 1.2×10⁻⁵ K⁻¹
at 700 °C was obtained.